Types of Asteraceae Plants in the Palangka Raya University Area (Indonesia) - Umi Novita Fitriah; Ria Windi Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Universitas Palangka Raya (UPR) campus, located adjacent to the Sebangau National Park, contains extensive green open spaces that support diverse plant communities, including the Asteraceae family. However, information regarding its diversity and potential utilization remains limited. This study aimed to inventory and identify Asteraceae species and describe their habitat distribution and potential uses within the UPR campus. An exploratory descriptive study with a field floristic approach was conducted from October 2025 to June 2026 using the exploration (cruise) method and purposive sampling. Species identification was based on morphological characteristics and validated using botanical references and the Plants of the World Online (POWO) database. A total of 10 Asteraceae species representing 10 genera were identified. Introduced species dominated the flora (80%), while native species accounted for only 20%. Most taxa occurred in disturbed habitats, including roadsides, drainage areas, agricultural fields, shrubs, and peatland transition zones. Several introduced species, including Praxelis clematidea, Chromolaena odorata, and Mikania micrantha, were identified as invasive weeds with allelopathic properties that may threaten native vegetation. Despite their invasive potential, Asteraceae species also possess significant economic and ecological value, including antioxidant, antibacterial, anti-inflammatory, and larvicidal properties, as well as applications as green manure and erosion-control ground cover. These findings provide baseline data for biodiversity management, invasive species monitoring, and the sustainable utilization of Asteraceae resources within the UPR campus.